Potential antibacterial activity of conventionally fermented pineapple peel extracts - Mansur, Sity Aishah; Norazhar, Nur Syifaa Sabeerah; A. Talip, Balkis (Penerbit UTHM, 2017)
Increasing demand of pineapple fruit in Malaysia as source of food has encouraged the development of technologies to speed up fruit extraction process and enhancing the economic growth of the government, farmers and local population. Nevertheless, other parts of the pineapple such as their skin, core and crown are usually disposed, leading to environmental pollution. Pineapple rind contains high amount of organic compounds, namely carbohydrates and this component has the potential to be the source of carbon in vinegar-producing fermentation process. To date, the knowledge of fermented pineapple peel extracts and its beneficial effects are limited. Therefore, this study is conducted to determine the characteristics of pineapple peel extract as well as its potential antimicrobial effects. Two types of pineapple peel are used in this study; the Josaphine and N36 and that both pineapple peels are capable of producing vinegar within 4 weeks of natural fermentation. In terms of physical properties, peel extracts from Josaphine are more turbid, have darker colour and higher moisture content than N36. In addition, Josaphine peel extracts are more acidic than N36, which probably contributed by the presence of higher concentration of organic acids. Antimicrobial tests show that N36 peel extracts are better at preventing the growth of Staphylococcus aureus (S. aureus) than Josaphine-derived vinegar. Additionally, both pineapple extracts had similar maximum inhibitory zone when tested with E.coli, indicating equal sensitivity of E.coli towards Josaphine- and N36-derived vinegars. This study synthesizes multipurpose vinegar from waste material and hopefully will provide useful information on the use of fermented pineapple peel in food or pharmaceutical industry.